Ureaplasma isolates differentially modulate growth factors and cell adhesion molecules in human neonatal and adult monocytes. (May 2018) - Glaser, Kirsten; Silwedel, Christine; Waaga-Gasser, Ana Maria; Henrich, Birgit; Fehrholz, Markus; Claus, Heike; Speer, Christian P.
Highlights: Differential modulation of growth factors and adhesion molecules by Ureaplasma . Dose-dependent induction of monocyte VEGF and ICAM-1 by Ureaplasma species. No impact of Ureaplasma isolates on monocyte G-CSF and VCAM-1. Enhanced neonatal ICAM-1 release upon co-infection with E. coli LPS and Ureaplasma . Abstract: Generally regarded as commensal bacteria, the pathogenicity of Ureaplasma has often been considered low. Controversy remains concerning the clinical relevance of Ureaplasma infection in the pathogenesis of inflammation-related morbidities. Recently, we demonstrated Ureaplasma -driven pro-inflammatory cytokine responses in human monocytes in vitro . We hypothesized that Ureaplasma may induce further inflammatory mediators. Using qRT-PCR and multi-analyte immunoassay, we assessed the expression of granulocyte-colony stimulating factor (G-CSF), vascular endothelial growth factor (VEGF), intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) in term neonatal and adult monocytes exposed to Ureaplasma urealyticum serovar 8 (Uu8) and U. parvum serovar 3 (Up3). Ureaplasma significantly induced VEGF mRNA in neonatal (Up3: p < 0.05, versus broth control) and adult monocytes (Uu8: p < 0.05) as well as ICAM-1 mRNA in neonatal cells ( p < 0.05 each). As far as protein expression was concerned, Up3 stimulated VEGF release in both monocyte subsets ( p < 0.01) and enhanced secretion of ICAM-1 protein in neonatal monocytes ( p < 0.05). In adult cells, ICAM-1 protein release was increased upon exposure to both isolates (Uu8: p < 0.05, Up3: p < 0.01). Ureaplasma -induced responses did not significantly differ from corresponding levels mediated by E. coli lipopolysaccharide (LPS). The stimulatory effects were dose-dependent. Ureaplasma infection, on the contrary, did not affect G-CSF and VCAM-1 expression. Of note, co-infection of LPS-primed neonatal monocytes with Ureaplasma enhanced LPS-induced ICAM-1 release (Uu8: p < 0.05). Our results confirm Ureaplasma -driven pro-inflammatory activation of human monocytes in vitro, demonstrating a differential modulation of growth factors and cell adhesion molecules, that might promote unbalanced monocyte responses and adverse immunomodulation.